Argumentación jurídica, graduación de penas en el robo con fuerza en el art. 189 del COIP, vulnera el principio de proporcionalidad - Chaguezá Quistanchala, Tania del Pilar (2017)
This research paper, entitled "Legal Argumentation: Gradation of Sentences for Robbery with Force in Article 189 of the COIP Violates the Principle of Proportionality," seeks to establish that judges impose excessive and disproportionate sentences on individuals who commit this crime, without taking into account the amount stolen, which in many cases does not exceed a basic unified salary, thus violating the principle of proportionality established in Article 76, paragraph 6, of the Constitution of the Republic of Ecuador. Within the Comprehensive Organic Criminal Code, regarding the crime of theft with force, there is a need to reform the second paragraph of Article 189, which establishes penalties of three to five years in prison for those who commit this crime. We believe that the application of penalties should take into account the value of the stolen goods and apply the principle of proportionality. Chapter 1 will address basic concepts to understand the content of the investigation on proportionality, procedural principles, criminal offenses, crimes, protected legal rights, penalties, and the purpose of penalties, compiling the necessary information to determine the origin and evolution of the current Comprehensive Organic Criminal Code. Chapter II will address the methodological framework through the use of scientific research methods, techniques, and instruments, which will allow for the proper establishment of results and justification of the existence of the problem posed. Chapter III will validate the research conducted, and this task will be carried out by experts in the field who will also agree on the proposed solution to this research problem.